Functional and Social Value of Chinese Brands. Issue 3 (27th May 2019) - Yang, Shuang; Jiménez, Fernando R.; Hadjimarcou, John; Frankwick, Gary L.
Abstract: An increasing popularity of Chinese brands around the world suggests that Chinese brands are beginning to overcome unfavorable country-of-origin (COO) effects. However, whether the perception of the functional and/or the social value of Chinese brands has improved remains unclear. Based on the theory of reasoned action, this study develops a theoretical framework to explain how consumers' perceptions of functional and social attributes affect purchase intentions of Chinese brands. Survey data were collected from an individualistic (US) and a collectivistic (Mexico) country. Results show that perceptions of functional value antecede attitudes towards the brand while perceptions of social value antecede social norms. The effect of social norms on purchase intention is stronger in the US than in Mexico. Recommendations for managers of Chinese brands, and brands from other emerging markets, are provided.